1961
DOI: 10.1021/ac60176a002
|View full text |Cite
|
Sign up to set email alerts
|

Emission Spectrometric Determination of Oxygen in Niobium Metal

Abstract: The emission spectrometric technique for the determination of oxygen in metals has been extended to the determination of oxygen in niobium. A d.c. carbon-arc discharge is used to extract the oxygen content of the sample as carbon monoxide into a static argon atmosphere. Special electrode assemblies which support a platinum-niobium alloy or provide a critical graphite-niobium re.'afionship are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1962
1962
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Previous work in gas and liquid chromatography with unsorbed solutes (3,11,12) has indicated that the curves of A vs. v for different values of p when plotted on a logarithmic scale, are parallel over at least a 100-fold range of v. At a constant value of v, A increases with p, at least up to a certain limiting value of p.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work in gas and liquid chromatography with unsorbed solutes (3,11,12) has indicated that the curves of A vs. v for different values of p when plotted on a logarithmic scale, are parallel over at least a 100-fold range of v. At a constant value of v, A increases with p, at least up to a certain limiting value of p.…”
mentioning
confidence: 94%
“…Much theoretical work has been carried out on the dependence of H upon fluid velocity and column parameters, see (7) and (2), and attempts have been made to define the requirements for minimum time analysis (7,(3)(4)(5). There is still, however, a lack of high quality experimental data.…”
mentioning
confidence: 99%
“…Short-cut methods are desired. In silicate determinations, the phosphate interference can be avoided by proper pH control (5) or by destroying the molybdophosphoric acid complex with oxalic acid (9).…”
Section: Thesementioning
confidence: 99%
“…Several chambers for the arc-extraction of gases from metals have been described. The typical chamber consists of a vacuum tight enclosure containing a horizontal rotating electrode stage with which a number of sample electrodes can be rotated into arcing position (3). Regardless of whether a gas-chromatographic or spectrometric analytical method is used, it is advantageous in theory to keep the chamber volume small to reduce dilution of the extracted gases.…”
mentioning
confidence: 99%
“…The electrode stage is rotated in a vertical plane through a gear set [2] (recessed into cover plate) and knob [3], The chamber was used initially with the 5-electrode stage [4], The 10-electrode stage [5] was constructed later and observations with it suggested that a 15-electrode stage could very probably be accommodated in the same compact chamber without danger of arc-over to adjacent electrodes. A telescoping, sample loading arm [6], which penetrates the rear of the chamber [7], provides storage for ten samples.…”
mentioning
confidence: 99%